DEVELOPMENT OF METHODS FOR CALCULATING FOUNDATION SLABS CONSIDERING THE STABILITY OF SUPERSTRUCTURES AND COMPLEX GROUND CONDITIONS - Otajonov Muslimbek Nazirjon o’g’li; Mahmudov Said Mahmudovich (PEDAGOGS, 2024)
This article explores modern methods for designing and analyzing foundation slabs, focusing on maintaining the stability of buildings in challenging ground conditions. It addresses key issues such as variable soil properties, the impact of groundwater, seismic forces, and long-term settlement. By highlighting the close relationship between foundation slabs and the structures they support, the article emphasizes the need for integrated design approaches. Innovations like Finite Element Analysis (FEA), advanced soil testing methods, geotechnical software, and performance-based design are discussed, along with real-world examples such as the Burj Khalifa and Tokyo Skytree. The article also looks at future trends, including sustainable materials, artificial intelligence, and smart monitoring systems, aiming to balance technological advancements with practical applications for a more resilient and sustainable construction industry.